Investigating the Relationship between Work-To-Family Conflict, Job Burnout, Job Outcomes, and Affective Commitment in the Construction Industry - Liu, Cong (Int J Environ Res Public Health, 2020)
This study explored the effects of work-to-family conflict on job burnout and job outcomes in the construction industry, focusing on the moderating effects of affective commitment. Based on the conservation of resources theory, a theoretical model introducing affective commitment as a moderating variable was established. A structured questionnaire survey was then implemented among construction professionals in China. A total of 376 valid responses were obtained. Structural equation modeling was used to analyze the valid data. The results revealed the following: (i) work-to-family conflict has a significant positive impact on job burnout, but a significant negative impact on job satisfaction and job performance; (ii) job burnout negatively affects job satisfaction and job performance; (iii) affective commitment negatively moderates the effects of work-to-family conflict on job burnout. This study provides a reference for construction companies to manage work-to-family conflict and job burnout of employees, while also improving their affective commitment and job outcomes.